Lifelines - Solomon, Harris (Duke University Press, 2022)
Harris Solomon takes readers into the trauma ward of one of Mumbai's busiest public hospitals, narrating the stories of the patients, providers, families, and frontline workers who experience and treat traumatic injury from traffic .